Β‐Catenin modulation in neurofibromatosis type 1 bone repair: therapeutic implications. Issue 9 (15th June 2016) - Ghadakzadeh, Saber; Kannu, Peter; Whetstone, Heather; Howard, Andrew; Alman, Benjamin A.
ABSTRACT: Tibial pseudarthrosis causes substantial morbidity in patients with neurofibromatosis type 1 (NF1). We studied tibial pseudarthrosis tissue from patients with NF1 and found elevated levels of b‐catenin compared to unaffected bone. To elucidate the role of b‐catenin in fracture healing, we used a surgically induced tibial fracture modelinconditionalknockout(KO)Nfl ( Nf1 flox/flox ) mice. When treated with a Cre‐expressing adenovirus (Ad‐Cre), there was a localized knockdown of Nf1 in the healing fracture and a subsequent development of a fibrous pseudarthrosis. Consistent with human data, elevated b‐catenin levels were found in the murine fracture sites. The increased fibrous tissue at the fracture site was rescued by local treatment with a Wingless‐type MMTV integration site (Wnt) antagonist, Dickkopf‐1 (Dkk1). The murine pseudarthrosis phenotype was also rescued by conditional b‐catenin gene inactivation. The number of colony‐forming unit osteoblasts (CFU‐Os), a surrogate marker of undifferentiated mesenchymal cells able to differentiate to osteoblasts, correlated with the capacity to form bone at the fracture site. Our findings indicate that the protein level of b‐catenin must be precisely regulated for normal osteoblast differentiation. An up‐regulation of b‐catenin in NF1 causes a shift away from osteoblastic differentiation resulting in a pseudarthrosis in vivo . These results support the notion that pharmacological modulation of b‐catenin can be used to treat pseudarthrosis in patients with NF1.—Ghadakzadeh, S., Kannu, P., Whetstone, H., Howard A., Alman, B. A. β‐catenin modulation in neurofibromatosis type 1 bone repair: therapeutic implications. FASEB J. 30, 3227–3237 (2016). www.fasebj.org